Seismic Behavior of Reinforced Masonry Structure: Relation between the Behavior Factor and the Ductility - Ourida Hellal Sfaksi; Ali Bouheraoua; Hacène Ait Aider; Mohamed O. Mechiche (Civil Engineering Journal, 2022)
The present work concerns a numerical study of the behavior of reinforced masonry (RM) structures under seismic loading. These structures are made of small hollow elements with reinforcements embedded in the horizontal joints. They were dimensioned according to the rules and codes commonly used. They are subject to vertical loads due to their own weight, and to horizontal loads due to seismic forces introduced by the accelerograms. The software used is the non-linear analysis program Drain2D, based on the finite element method, where the shear panel element was introduced. A series of calculations was performed on a number of structures at different levels, excited by three major accelerograms (El Centro, Cherchell, and Kobe). Throughout the study, our main interest is to evaluate the behaviour factor, the ductility, and the failure mode of these structures while increasing the intensity of earthquakes introduced. The results of this present study indicate that the average values of the behaviour factor and the global ductility are of the order of q≈μ≈3.00. The reinforced masonry structures studied have been broken by interstage displacement. The results given by the study are comparable to those given in the literature and in Eurocode 8. The behavior of reinforced masonry under a seismic load is similar to the behavior of reinforced concrete; it is a ductile behavior that allows the dissipation of the energy transmitted by the earthquake. These numerical studies confirm and complete the experimental work carried out by other researchers. Doi: 10.28991/CEJ-2022-08-10-012 Full Text: PDF